1990
DOI: 10.1557/jmr.1990.0498
|View full text |Cite
|
Sign up to set email alerts
|

Amorphization and disordering of the Ni3Al ordered intermetallic by mechanical milling

Abstract: The ordered fcc intermetallic compound Ni3Al was mechanically milled in a high energy ball mill. The severe plastic deformation produced by milling induced transformations with increasing milling time as follows: ordered fcc → 2; disordered fcc → 2; nanocrystalline fcc + amorphous. The milling time for complete disordering occurred at 5 h for stoichiometric Ni3Al milled at ambient temperature compared to 50 h for the first observation of an amorphous structure. The structural and microstructural evolution with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(73 citation statements)
references
References 33 publications
8
64
0
1
Order By: Relevance
“…As Ni 3 Al is ordered up to the melting point, disordered Ni 3 Al needs to be produced by vapor deposition [29] or ball milling [30]. Both of these methods produce a material with a very small grain size (respectively, 4 nm [29] and 7 nm [31]).…”
mentioning
confidence: 99%
“…As Ni 3 Al is ordered up to the melting point, disordered Ni 3 Al needs to be produced by vapor deposition [29] or ball milling [30]. Both of these methods produce a material with a very small grain size (respectively, 4 nm [29] and 7 nm [31]).…”
mentioning
confidence: 99%
“…28,29) It has been found that the accumulation of structure defects, such as vacancies, dislocations, grain boundaries and distortion of lattice and the refinement of grain lead to the increase of the Gibbs free energy of crystalline phase. 30,31) If the free energy of crystalline phase is higher than that of the glassy phase, the transformation to the glassy state can be expected.…”
Section: Resultsmentioning
confidence: 99%
“…• Contrary, Jang et al [10] observed a complete disordering by ball milling of the ordered Ni3 A1 intermetallic compound which has an L12 (ordered fcc) crystal structure. The value of LRO parameter S decreases monotonically from 1 to O after several hours of processing.…”
Section: Disordering By Mechanical Milling •mentioning
confidence: 94%